Developmental aspects of reading motivation and reading achievement among second grade low achievers and typical readers. (14th June 2017) - Vaknin‐Nusbaum, Vered; Nevo, Einat; Brande, Sigi; Gambrell, Linda
Abstract : This investigation examined developmental aspects of 155 second‐graders' intrinsic reading motivation and reading achievement at the beginning and end of a school year. Reading motivation remained at the same level through the school year, while reading achievement was significantly higher at the end of it than at the beginning. According to word reading skills, low reading achievers ( n  = 63) and typical readers ( n  = 92) evinced significant differences in reading motivation. The former scored lower in overall reading motivation and self‐concept as a reader, as well as in reading achievement. Throughout the school year, low reading achievers showed a decline in overall motivation, self‐concept as a reader and literacy outloud, and did not improve in reading comprehension achievement. Reading motivation in typical readers remained high and steady during the school year. Implications of the results are discussed in relation to previous studies.